Acceptability and awareness of intrauterine contraceptive device among reproductive age women - Ramkumar, S.; Vijayalakshmi, S.; Soundararajan, R.; Elakkiyachelvi, M.; Elakkiya, E.; Fathima, S. (International Journal Of Community Medicine And Public Health, 2021)
Contraception is the intentional prevention of conception through the use of various devices, sexual practices, chemicals, drugs or surgical procedures. An effective contraception allows a physical relationship without fear of an unwanted pregnancy and ensures freedom to have children when desired. In this article we are going to see their utilization and awareness about usage of intrauterine contraceptive device (IUCD).